ARIES: lounge chair / Nur Fatin Aniesya Azizul Aziz - Azizul Aziz, Nur Fatin Aniesya (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
ARIES is a large, durable, and cozy lounge chair designed from the form inspired by the spiralling curves of a ram's horns. This lounge chair is designed for its enjoyers to relax and unwind at any time they wish to do so. The purpose of the lounge chair is to accommodate a range of preferences, styles, and functions. Lounge chairs are often used in spaces where posture relaxation often occurs such as in homes, offices, waiting rooms and communal spaces. They're not designed for work or productivity, but rather relaxation. The aim is to design a traditional lounge chair that implements the inspirations taken from a ram and has a slightly complex classical design that allow users to spend their time with leisure. This lounge chair makes a perfect addition to home living rooms and lounges in residential areas. The design adds a spark of nature into their homes as the organic shapes and natural-looking finishing complement almost any living room. Based on studies and research conducted, having biophilic design (incorporation of natural elements such as wood) items in a household can improve one's overall wellbeing. The inclusion of these natural elements is shown to aid in reducing stress, improve creativity and mental clarity. It is hoped that ARIES can not only be an item of furniture, but also a place for people to relax and unwind after they spend their day and want to have some time with themselves, be it for a nap, a short read, or even while enjoying a warm cup of tea.